From Ghosts to Gifts: Weaving Land, Memory, and Care into Curriculum - Chartrand, Cindy (Pawaatamihk, 2025)
This paper explores curriculum as a living, relational practice grounded in Métis knowledge, personal narrative, and poetic inquiry. Framed by the metaphor of ghosts and gifts, it reimagines curriculum as ceremony—a sacred process of remembering what was erased, honouring the spirit of the child, and centring kinship, care, and land. By weaving together Indigenous story, blood memory, maternal pedagogy, and speculative imagination, the paper challenges colonial logics of standardization and deficit. It affirms curriculum’s transformative potential when rooted in love, imagination, and sacred relationality, offering pathways for healing, resurgence, and dreaming otherwise in educational practice.